2021
DOI: 10.1111/1475-6773.13711
|View full text |Cite
|
Sign up to set email alerts
|

Paying patients to use lower‐priced providers

Abstract: Objective: Many employers have introduced rewards programs as a new benefit design in which employees are paid $25-$500 if they receive care from lower-priced providers. Our goal was to assess the impact of the rewards program on procedure prices and choice of provider and how these outcomes vary by length of exposure to the program and patient population.Study Setting: A total of 87 employers from across the nation with 563,000 employees and dependents who have introduced the rewards program in 2017 and 2018.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…48 These benefit designs give consumers an incentive to choose lower cost providers, but they vary in the information given to consumers. Price information alone can be useful for a single service such as an MRI or total knee replacement, [49][50][51][52][53] but price information needs to be accompanied by an incentive to use the information, 54,55 and the most important question with respect to affordability may not be the price of the MRI, but whether the consumer is likely to benefit from an additional MRIa question concerning the quantities of prescribed services.…”
Section: Discussionmentioning
confidence: 99%
“…48 These benefit designs give consumers an incentive to choose lower cost providers, but they vary in the information given to consumers. Price information alone can be useful for a single service such as an MRI or total knee replacement, [49][50][51][52][53] but price information needs to be accompanied by an incentive to use the information, 54,55 and the most important question with respect to affordability may not be the price of the MRI, but whether the consumer is likely to benefit from an additional MRIa question concerning the quantities of prescribed services.…”
Section: Discussionmentioning
confidence: 99%
“…Whaley et al found in a separate study analyzing data from 2017 to 2018 that prices decreased for beneficiaries in employer-sponsored plans that received a financial payment to choose care from lower-cost providers and that the effects were most concentrated among imaging studies, specifically magnetic resonance imaging (MRI) studies. 31 This again suggests that consumers can respond to price transparency initiatives when they are incentivized. However, consumers may not be the only market actors to respond to prices becoming publicly available.…”
Section: Background: Historical Perspectives In Academic Literaturementioning
confidence: 99%
“… 15 Another recent study by Whaley et al using employer data from 2017 to 2018 saw significant reduction prices for imaging but no effect on utilization if consumers were given incentives to shop for care. 16 Results from 2010 to 2016 study by Gourevitch et al found the proportion of pregnant individuals who sought price information before childbirth more than doubled within the first 6 years of availability of a price transparency tool. These findings suggest that price information may help individuals anticipate their out-of-pocket childbirth costs.…”
Section: Policy Backgroundmentioning
confidence: 99%